Features of the development of franchising in small business in Kazakhstan (Journal of Economic Research & Business Administration, 2015)
Considerable part of businessmen in the developed countries work under the franchising contract. This is the results of the fact that franchising is an effective way of conducting small and middle-sized business when a franchisee constantly gets support from the franchiser. Buying the franchize, even a beginner businessman has opportunity to organize his business competently which will start making profit in the shortest terms. Kazakhstan as a сountry with developing economy has huge opportunities for business development on the basis of franchasing systems. The market of Kazakhstan which is not filled in this plan isn’t attractive, thus new business technologies can come to the country as the share of small and middle-sized business has to be enlarged. Franchising has already revealed its potential in Kazakhstan. Many foreign companies are developing in Kazakhstan on the terms of providing franchise. A series of domestic companies are realizing their own franchasing programs. However, rate of franchising development can be accelerated as it will become a powerful contribution to further prosperity of the country, strengthening the business and satisfaction of people’s needs.
Keywords: market; small and middle-sized business; franchising; development of franchasing relations; the franchisor; sub-franchisees; brand; public support